Anterior Skull Base Reconstruction: Does Fat Preparation Matter? - Wood, Joshua; Densky, Jaron; Boughter, John; Sebelik, Merry; Shires, Courtney (Journal of Neurological Surgery Reports, 2018)
Objectives This article aims (1) to determine whether there is any difference in cerebrospinal fluid (CSF) leak rate after anterior skull base autologous fat reconstruction based on how the fat is prepared, and (2) to measure impact on surgical times by reconstruction type.Design Translational animal model surgical technique 3-arm trial, comparing two different methods of autologous fat skull base reconstruction versus a nonreconstructed control group.Setting Animal study.Subjects Adult Sprague-Dawley rats.Main Outcome Measures Resolution of CSF rhinorrhea after repair of a surgically created anterior skull base defect.Results Both wet (uncompressed) and dry (compressed) fat reconstruction of an anterior skull base defect demonstrated lower CSF leak rates than nonreconstructed defects. Dry fat reconstruction achieved significance in superiority of controlling CSF leak over no reconstruction (64% success vs. 31%); while wet fat reconstruction trended toward significance (50% vs. 31%). Reconstruction procedure time was longer than nonreconstructed controls, but there was no significant difference between type of fat preparation in surgical time.Conclusions This study demonstrates that drying and compressing the fat graft improves autologous fat reconstruction success for anterior skull base defects, and does not add significantly to surgical time over nonprepared fat.
Keywords: autologous fat graft; cerebrospinal fluid leak; anterior skull base; skull base reconstruction